Build your running body : a total-body fitness plan for all distance runners, from milers to ultramarathoners : run farther, faster, and injury-free - Magill, Pete; Schwartz, Thomas; Breyer, Melissa, 1957- (The Experiment, 2014)
Whether you're a miler or an ultramarathoner, if you want a fit, fast, and injury-resistant running body, there's a better way to train than relentlessly pursuing mileage. This easy-to-use workout manual draws on the latest research in running physiology to target all the components that go into every stride--including muscles, connective tissue, cardiovascular fitness, energy production, the nervous system, hormones, and the brain. With the breakthrough whole-body training program in Build Your Running Body, runners will improve their times, run longer and more comfortably, and reduce injury.